2015
DOI: 10.1142/s0217590815500356
|View full text |Cite
|
Sign up to set email alerts
|

Singapore's Demographic Transition, the Labor Force and Government Policies: The Last Fifty Years

Abstract: The trajectory of Singapore's population size and composition can be mapped out with its progression through the various phases of demographic transition from high birth and death rates in the post-war years to very low birth and death rates today, all within the context of rapid economic and social development that has taken place in the past 50 years. Population planning has been integral in Singapore's national development strategy, balancing the economy's needs for more and better qualified workers with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The mean years of schooling for non‐students aged 25 and over were 5.6 and 3.7 years for male and female, respectively. In 2010, the ratios increased to 10.6 and 9.7 years, respectively (Yap and Gee ). In 1980, among all employees aged 15 and over, 20 per cent of male employees and 13.9 per cent of female employees were professional, managerial and technical workers.…”
Section: Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean years of schooling for non‐students aged 25 and over were 5.6 and 3.7 years for male and female, respectively. In 2010, the ratios increased to 10.6 and 9.7 years, respectively (Yap and Gee ). In 1980, among all employees aged 15 and over, 20 per cent of male employees and 13.9 per cent of female employees were professional, managerial and technical workers.…”
Section: Educationmentioning
confidence: 99%
“…In 1980, among all employees aged 15 and over, 20 per cent of male employees and 13.9 per cent of female employees were professional, managerial and technical workers. In 2010, the ratios increased to 54.1 per cent and 49.3 per cent, respectively (Yap and Gee ). At present, the government spends approximately 20 per cent of its budget on education (figure ).…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…This contributed to opposition party electoral and parliamentary gains in the 2011 general election (and subsequent by-elections). Various surveys since then have shown that a very high proportion of Singaporeans ("nearly 9 in 10") believe that the number of foreign workers should be reduced (Wong, 2013), and this proportion has remained high despite the government's policy response to tighten (but not reduce) inflows. 26 In February 2012, Deputy Prime Minister and Finance Minister Tharman Shanmugaratnam said, "We have to reduce our dependence on foreign labor, and do much more to build an economy driven by higher skills, innovation and productivity."…”
Section: Growth With Low Productivitymentioning
confidence: 99%
“…Better we have fewer foreign workers and let our wages rise." 14 Department of Statistics and Ministry of Manpower Yap and Gee (2015). in this volume note that FLFP in Singapore does not increase after children are older, as it does in most other high-income countries.…”
mentioning
confidence: 95%